Ghana - Establishment of the Commercial Court - Cofie, Sandra (World Bank, Washington, DC, 2012)
An often-repeated remark about George Kingsley Acquah, Ghana's chief justice from 2003 until 2007 and driver of his country's major judicial reforms was that "it took a man like him for this to happen". The author certainly subscribe to this view, having observed his impact from position as director of the judicial reform, project development and implementation unit at the judicial service of Ghana. Doubtless, most prominent reform is the establishment of the commercial division at the High Court in Accra, the first commercial court in Ghana, and possibly the most significant addition to the judicial service since independence. After decades of political turmoil that had left behind a disrupted court system, the reform not only brought about shorter delays to commercial dispute resolution. It also instilled new spirit in Ghana's justice sector. In light of Ghana's policy objective of becoming a middle income country by 2020, the state of legal affairs looked dire a mere 10 years ago. Military rule had given way to an emerging democracy only in the 1990s. In 1982, three judges had been murdered, and the following years witnessed a severe lack of judicial personnel and resources. More than half of posts in district courts were vacant, backlog and delays in adjudication persistent. The legal system was a slow, erratic, inconsistent and costly environment, hostile to the effective performance of the judicial function. Ghanaian businesses suffered: diagnosis of the commonwealth secretariat and the World Bank described contract enforcement as generally inadequate. Long delays and corruption made uncertainty in contract enforcement pervasive and posed a major obstacle to doing business in Ghana.